Mechanism of mineral phase transformation in preparing aluminum alloy by electrolysis of molten salt from aluminum alloy dross - Zhengping Zuo; Wenfen Wu; Jianbo Zhang; Zhanbing Li; Fengqin Liu; Shaopeng Li (Alexandria Engineering Journal)
The electrochemical reduction method is an effective approach for the harmless treatment of toxic components in aluminum alloy dross (AAD) and the high-value utilization of valuable elements. By combining theoretical calculations and experiments, this paper reveals the migration behavior and transformation laws of toxic and valuable elements in AAD during hydrolysis, calcination, and electrolysis. The removal rates of N and Cl in hydrolysis were 88.01 % and 93.84 %, respectively. During calcination, Al(OH)3 was transformed into γ-Al2O3, and part of the aluminum alloy phase and Si monomers were oxidized into oxides. During electrolysis, all positive elements (such as Fe, Si, Cu, and Zn, which are more electronegative than aluminum) were incorporated into the aluminum alloy. A very small portion of Mg and Ca entered the aluminum alloy, but most of the Mg and Ca were respectively transformed into MgF2 and CaF2, gradually accumulating in the electrolyte. The toxic components N and Cl were converted into useful by-products throughout the entire process. Moreover, other valuable components entered the aluminum alloy, no other pollutants were generated, and the overall recovery rate was more than 95 %. The results of this study provide theoretical support for developing similar electrochemical disposal techniques for solid waste.